Waste oil management in the auto-repair and maintenance workshops in the informal sector of Harare, Zimbabwe - Jerie, Steven (Midlands State University, 2017)
A publication by Professor Steven Jerie a Lecturer in the Department of Geography and Environmental Studies Midlands State University, Zimbabwe